2021
DOI: 10.1002/jgm.3368
|View full text |Cite
|
Sign up to set email alerts
|

Fiber modifications enable fowl adenovirus 4 vectors to transduce human cells

Abstract: Background: Pre-existing immunities hamper the application of human adenovirus (HAdV) vectors in gene therapy or vaccine development. Fowl adenovirus (FAdV)based vector might represent an alternative. Methods: An intermediate plasmid containing FAdV-4 fiber genes, pMD-FAV4Fs, was separated from FAdV-4 adenoviral plasmid pKFAV4GFP. An overlap extension polymerase chain reaction (PCR) was employed for fiber modification in pMD-FAV4Fs, and the modified fibers were restored to generate new adenoviral plasmids thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 49 publications
(102 reference statements)
0
13
0
Order By: Relevance
“…Original FAdV-4 vectors could hardly transduce human cells. When FAdV4-CG, a recombinant FAdV-4 carrying GFP reporter gene, was used at an MOI of 1000 vp/cell, less than 4% of 293 cells were detected to express GFP [ 21 ]. In order to increase the transduction of FAdV-4 to human cells, RGD4C peptide was inserted to the CD, DE, HI and IJ loops of FAdV-4 fiber1 knob to generate fiber-modified viruses in a previous study [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Original FAdV-4 vectors could hardly transduce human cells. When FAdV4-CG, a recombinant FAdV-4 carrying GFP reporter gene, was used at an MOI of 1000 vp/cell, less than 4% of 293 cells were detected to express GFP [ 21 ]. In order to increase the transduction of FAdV-4 to human cells, RGD4C peptide was inserted to the CD, DE, HI and IJ loops of FAdV-4 fiber1 knob to generate fiber-modified viruses in a previous study [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…The gene transfer ability of FAdV-4 vector to human cells was very low. We tried to insert RGD4C peptide to the fiber1 knob and replace the knob of fiber2 with that from HAdV-35 fiber, such modification substantially improved the gene transduction of FAdV-4 to human adherent or suspension cell lines [ 21 , 22 , 23 ]. However, the activity of current FAdV-4 vectors still did not meet the requirement of transducing human cells.…”
Section: Introductionmentioning
confidence: 99%
“…Whether the recombinant virus FAdV4-RFP_F1 with the edited fiber-1 can alter the tissue tropism in vivo needs to be elucidated. Recently, although Zhang et al showed that the knob of Fiber-1 could also be edited to insert the exogenous peptide, several generated recombinant viruses could alter the cell tropism in vitro ( 18 ). To investigate the mechanism for the protective efficacy for FAdV4-RFP_F1 against FAdV-4, the sera from chickens before challenge were collected and tested for neutralizing antibody.…”
Section: Discussionmentioning
confidence: 99%
“…Mastadenoviruses, especially human adenovirus C (HAdV-C), have been intensively studied and constructed as gene transfer vectors ( 2 4 ). The application of HAdV-based vectors in human gene therapy and vaccine development has been hindered by high prevalence of pre-existing immunities against these pathogens in humans ( 5 , 6 ), and interest has been attracted to construct recombinant fowl adenoviruses (FAdVs), a subgroup of aviadenoviruses, as gene delivery tools ( 7 9 ).…”
Section: Introductionmentioning
confidence: 99%